2014
DOI: 10.1186/1471-2393-14-129
|View full text |Cite
|
Sign up to set email alerts
|

Birth Preparedness and Complication Readiness (BPCR) interventions to reduce maternal and neonatal mortality in developing countries: systematic review and meta-analysis

Abstract: BackgroundBirth Preparedness and Complication Readiness (BPCR) interventions are widely promoted by governments and international agencies to reduce maternal and neonatal health risks in developing countries; however, their overall impact is uncertain, and little is known about how best to implement BPCR at a community level. Our primary aim was to evaluate the impact of BPCR interventions involving women, families and communities during the prenatal, postnatal and neonatal periods to reduce maternal and neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 30 publications
(69 reference statements)
5
107
0
4
Order By: Relevance
“…Based on the findings of this study, it is important to know and implement interventions aimed at improving survival among preterm patients, such as specialized care during pregnancy and labor, 2,18,19 antenatal corticosteroid use, 20 and breastfeeding in the first 24 hours, 21 and to increase the resources allocated to health care. 22,23 The limitations of this study are that it was conducted in a hospital sample that may be different from the general population and that the sample was too small to establish specific subgroups, such as mothers < 15 years or who received no antenatal care at all.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of this study, it is important to know and implement interventions aimed at improving survival among preterm patients, such as specialized care during pregnancy and labor, 2,18,19 antenatal corticosteroid use, 20 and breastfeeding in the first 24 hours, 21 and to increase the resources allocated to health care. 22,23 The limitations of this study are that it was conducted in a hospital sample that may be different from the general population and that the sample was too small to establish specific subgroups, such as mothers < 15 years or who received no antenatal care at all.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses showed that exposure to BP/CR interventions was associated with a statistically significant reduction of 18% in neonatal mortality risk (twelve studies, RR = 0.82; 95% CI: 0.74, 0.91) and a non-significant reduction of 28% in maternal mortality risk (seven studies, RR = 0.72; 95% CI: 0.46, 1.13) [13]. …”
Section: Introductionmentioning
confidence: 99%
“…4 En pacientes del HCGJIM, no se observó que la edad materna, su escolaridad, el estado civil o la presencia de factores de riesgo, como infección urinaria, ruptura prematura de membranas o corioamnionitis, incrementaran el riesgo de muerte. Dados los hallazgos de este estudio, es importante conocer e implementar intervenciones para mejorar la supervivencia de pacientes prematuros, como la atención especializada del embarazo y el trabajo de parto, 2,18,19 el uso de corticoides prenatales, 20 la lactancia materna en las primeras 24 horas de vida, 21 e incrementar los recursos en cuidados a la salud. 22,23 Las limitaciones de esta investigación son el haberse realizado con una muestra hospitalaria que puede ser diferente a la población general y un tamaño de muestra insuficiente para subgrupos específicos como son madres < 15 años o con nulo control prenatal.…”
Section: Discussionunclassified